2014
DOI: 10.1002/ana.24214
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil does not improve cardiomyopathy in Duchenne/Becker muscular dystrophy

Abstract: Objective Duchenne and Becker muscular dystrophy (DBMD) are allelic disorders caused by mutations in dystrophin. Adults with DBMD develop life-threatening cardiomyopathy. Inhibition of phosphodiesterase 5 (PDE5) improves cardiac function in mouse models of DBMD. To determine if the PDE5-inhibitor sildenafil benefits human dystrophinopathy, we conducted a randomized, double-blind, placebo-controlled trial (ClinicalTrials.gov, number NCT01168908). Methods Adults with DBMD and cardiomyopathy (ejection fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 43 publications
1
64
0
Order By: Relevance
“…Such studies have yielded mixed results in animal models, with modest improvements in cardiac function and pathology. Furthermore, human trials have offered little evidence of a beneficial cardiac effect of sildenafil treatment in adults with DMD or Becker muscular dystrophy (58,59). In light of our findings, it is possible that the shortcomings of these previous studies reflect the existence of other functional targets of muscle-derived NO, or additional targets of altered AMPK regulation, that contribute to dysfunction in dystrophic muscle (43,60,61).…”
Section: Discussionmentioning
confidence: 63%
“…Such studies have yielded mixed results in animal models, with modest improvements in cardiac function and pathology. Furthermore, human trials have offered little evidence of a beneficial cardiac effect of sildenafil treatment in adults with DMD or Becker muscular dystrophy (58,59). In light of our findings, it is possible that the shortcomings of these previous studies reflect the existence of other functional targets of muscle-derived NO, or additional targets of altered AMPK regulation, that contribute to dysfunction in dystrophic muscle (43,60,61).…”
Section: Discussionmentioning
confidence: 63%
“…The reported reduced recruitment of sufficient blood flow in patients with BMD during muscle activity responsible for relative ischemia [37] is improved by PDE5 inhibition in some studies [22,38,39], but not in all of them [23,24], which may relate to variations in methods applied. Corresponding reduced brain blood flow recruitment during activation was hypothesized to be present in patients with BMD and restored by PDE5 inhibition; the current data partly support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil is used to treat erectile dysfunction and pulmonary hypertension, and works by augmenting endogenous cGMP levels, thus promoting a normal NO response. Recently sildenafil/PDE5 administration was shown to reduce skeletal muscle and cardiac dysfunction and to ameliorate dystrophy in a mouse model of DMD [20][21][22], although no positive effect was found on skeletal or cardiac muscle function and brachial arterial forearm flow in 17 patients with BMD [23] or 15 patients with BMD/DMD [24]. In healthy subjects, including males and females, sildenafil does not change the cerebral blood flow (CBF) after a single oral dose of 100 mg measured by single photon emission computer tomography and transcranial Doppler [25], but it may do so in patients with dysfunctional NO signaling [26], such as patients with BMD.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated that that both TRPC6 and m-calpain were increased in the myocardium of DMD patients, suggesting that the GRMD treatment effects can translate to DMD patients. The published clinical study with the short-acting PDE5 inhibitor sildenafil showed no efficacy in the DMD patients who were treated 10 ; however, those patients had decreased cardiac function on treatment initiation. The present data strongly support the prophylactic use of tadalafil to counter cardiomyopathy in DMD patients rather than treatment after pathology and functional decline are evident.…”
Section: Discussionmentioning
confidence: 99%
“…4 In models of heart failure, PDE5 inhibition has improved cardiomyopathy [5][6][7][8][9] ; however, a recent study of sildenafil in older (aged >15 years) DMD patients with clinical cardiomyopathy (ejection fraction ≤45%) failed to show any significant benefit with treatment for >6 months. 10 Sildenafil's lack of effectiveness in the above-mentioned DMD patient population does not eliminate the possibility that PDE5 inhibition could be prophylactic against cardiomyopathy development and progression if initiated early rather than being able to reverse preexisting pathology. In the current study, we tested this hypothesis using tadalafil, a PDE5 inhibitor that possesses a longer half-life than sildenafil (t 1/2 of 17.5 versus 4 hours for sildenafil).…”
mentioning
confidence: 99%